ADAPTATION OF LAMELLAR GILL MOLLUSKS TO THE PASSIVE LIFESTYLE OF BIOFILTERS - ARCHANA PRAKASH (International Journal of Multidisciplinary Research and Studies, 2020)
Lamellar gill mollusks, such as mussels and clams, are known for their ability to act as efficient biofilters in aquatic environments. They are able to passively filter large amounts of water, removing suspended particles and pollutants, and improving water quality for other organisms. The adaptation of these mollusks to the passive lifestyle of biofilters is evident in their anatomy and physiology. The gills of these animals are highly specialized structures that are adapted for filtration. They are composed of numerous thin, flat structures called lamellae, which increase the surface area available for filtration. The lamellae are lined with cilia, which create a current of water that flows through the gills, carrying suspended particles and pollutants with it. The particles are trapped in the mucus lining of the gills and are either ingested or expelled. In addition to their specialized gills, lamellar gill mollusks have adapted to their passive lifestyle by developing strong byssal threads. Byssal threads are secreted by the mollusk and used to anchor the animal to a substrate, such as a rock or a pier. This allows the animal to remain in one place while water flows over its gills, maximizing its ability to filter large amounts of water Overall, the adaptation of lamellar gill mollusks to the passive lifestyle of biofilters is a remarkable example of evolutionary adaptation. These animals have developed highly specialized structures and behaviors that allow them to efficiently filter large amounts of water, improving water quality for other organisms in the ecosystem.